THE RELATIONSHIP BETWEEN MACRONUTRIENT INTAKE, KNOWLEDGE, ATTITUDES AND BEHAVIORS OF MOTHERS WITH THE INCIDENCE OF STUNTING - Setia, Agustina; Saleh, Asmulyati S (Poltekkes Kemenkes Kupang, 2024)
Stunting is a condition of chronic malnutrition which will have an impacton the growth and development that occurs before birth. The research objective was to determine the relationship between macronutrient intake, knowledge, preparedness and maternal behavior with stunting in toddlers in Maulafa District, Kupang City in 2022. The Cluster Random Sampling technique was used in this study. The populasion is all to toddlers in Maulafa District, Kupang City, totaling 6103 toddlers. The number of participants is 100 toddlers. The researchwas conducted in December 2022-March 2023. A 24-hour recall form was used tpo obtain mavronutrieny intake. The results of interviews whit mothers produce knowledge, attitudes and behavior. Chi-square is used for statistical tests. Form the results of the study it was found that there were 28 stunded toddlers (28%) and 72 toddlers (72%) who were not stunded. According to the research results, the incidence of stunting in toddlers is related to the intake of macronutrients, knowledge, attitudes and behavior of the mothers with a P-value = < 0,005